2020
DOI: 10.1093/nutrit/nuaa037
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for dementia: a systematic review and meta-analysis of randomized controlled trials

Abstract: Context Dementia is the fifth leading cause of death in the world. Animal studies indicate that in addition to the aging process, intestinal microbiota may play an important role in the neurodegeneration process through the modulation of the gut-brain axis. Objective A systematic review and meta-analysis was conducted to determine the effectiveness of probiotic and synbiotic supplementation on the cognitive function of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 25 publications
2
35
0
2
Order By: Relevance
“…Another clinical trial showed that B. breve A1 supplementation may have beneficial effects on cognitive function in elderly Japanese subjects with memory complaints (Kobayashi et al, 2019). In three clinical randomized controlled trials, clinically confirmed patients with AD treated with probiotics (mainly Lactobacillus and Bifidobacterium strains) for 12 weeks showed no beneficial effect on cognitive function (Akbari et al, 2016;Krüger et al, 2021). This may be due to insufficient intervention period, different disease severity, and changes in dietary patterns.…”
Section: Probioticsmentioning
confidence: 99%
“…Another clinical trial showed that B. breve A1 supplementation may have beneficial effects on cognitive function in elderly Japanese subjects with memory complaints (Kobayashi et al, 2019). In three clinical randomized controlled trials, clinically confirmed patients with AD treated with probiotics (mainly Lactobacillus and Bifidobacterium strains) for 12 weeks showed no beneficial effect on cognitive function (Akbari et al, 2016;Krüger et al, 2021). This may be due to insufficient intervention period, different disease severity, and changes in dietary patterns.…”
Section: Probioticsmentioning
confidence: 99%
“…Consistent with the burgeoning interest, several reviews of the efficacy of probiotic supplementation for neurological disorders/AD have been published, including one systematic review [ 12 ] and three meta-analyses [ 13 , 14 , 15 ]. Despite providing comprehensive evaluations of the early literature in this field and their importance for guiding clinical trials, these reviews have several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite providing comprehensive evaluations of the early literature in this field and their importance for guiding clinical trials, these reviews have several limitations. For example, the meta-analyses yielded contradictory findings, with one reporting no ameliorative effect of probiotics on cognitive function [ 13 ] and the other two reporting improvement in cognitive function after the administration of probiotics [ 14 , 15 ]. These meta-analyses only included studies published before 2018 that investigated the beneficial effects of probiotics and prebiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, restoring normal microbiota allowed the recovery of intestinal inflammation [ 181 ] and alterations in glucose homeostasis [ 182 ], suggesting that interventions aimed at eubiosis may target both metabolic and neurodegenerative processes. Up to now, three clinical trials investigated the effects of a 12-weeks course of probiotics consisting of Lactobacillus and Bifidobacterium strains [ 183 ]. Unfortunately, they were unable to demonstrate strong efficacy on cognitive function, although they may improve markers of lipid profile and insulin resistance.…”
Section: Roles Of Diet and Microbiota In Neurodegenerative Diseasementioning
confidence: 99%